A novel imaging method revealed phosphatidylinositol 3,5-bisphosphate-rich domains in the endosome/lysosome membrane - Sho Takatori; Toyoshi Fujimoto (Communicative & Integrative Biology, 2016)
We developed a new method to observe distribution of phosphatidylinositol 3,5-bisphosphate [PtdIns(3,5)P2] using electron microscopy. In freeze-fracture replicas of quick-frozen samples, PtdIns(3,5)P2 was labeled specifically using recombinant ATG18 tagged with glutathione S-transferase and 4×FLAG, which was mixed with an excess of recombinant PX domain to suppress binding of ATG18 to phosphatidylinositol 3-phosphate. Using this method, PtdIns(3,5)P2 was found to be enriched in limited domains in the yeast vacuole and mammalian endosomes. In the yeast vacuole exposed to hyperosmolar stress, PtdIns(3,5)P2 was distributed at a significantly higher density in the intramembrane particle (IMP)-deficient liquid-ordered domains than in the surrounding IMP-rich domains. In mammalian cells, PtdIns(3,5)P2 was observed in endosomes of tubulo-vesicular morphology labeled for RAB5 or RAB7. Notably, distribution density of PtdIns(3,5)P2 in the endosome was significantly higher in the vesicular portion than in the tubular portion. The nano-scale distribution of PtdIns(3,5)P2 revealed in the present study is important to understand its functional roles in the vacuole and endosomes.